2002
DOI: 10.1002/ar.a.10019
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐mediated effects of nicotine and its nitrosated derivative NNK on pulmonary neuroendocrine cells

Abstract: Pulmonary neuroendocrine cells (PNECs) have been implicated in the development of small cell lung carcinoma (SCLC) and pediatric asthma, and smoking is a risk factor for both diseases. We as well as others have shown that the ␣ 7 nicotinic acetylcholine receptor (␣ 7 nAChR) regulates the release of 5-hydroxytryptamine (5-HT, serotonin) in PNECs and SCLC. Serotonin is an autocrine growth factor for PNECs and SCLC and acts as bronchoconstrictor. We found that nicotine and its nitrosated carcinogenic derivative 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 45 publications
3
89
0
3
Order By: Relevance
“…NNK binds to and activates the ␣ 7 nAChR resulting in the opening of voltage-gated ion channels, the influx of Ca 2ϩ , and the activation of protein kinase C, which can trigger the Raf/ MEK/ERK1/2 protein kinase cascade in SCLC (23,29). Evidence reported here suggests that MAPKs ERK1 and -2 are physiological calpain kinases because NNK can potently activate ERK1 and -2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NNK binds to and activates the ␣ 7 nAChR resulting in the opening of voltage-gated ion channels, the influx of Ca 2ϩ , and the activation of protein kinase C, which can trigger the Raf/ MEK/ERK1/2 protein kinase cascade in SCLC (23,29). Evidence reported here suggests that MAPKs ERK1 and -2 are physiological calpain kinases because NNK can potently activate ERK1 and -2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, phosphorylation, in addition to Ca 2ϩ binding, may be another important mechanism for activation of calpains. Because ERK1 and ERK2 function as physiologic calpain kinases (22) and NNK potently activates these two protein kinases in human lung cancer cells (2,23), NNK may promote lung cancer cell migration and invasion in a mechanism involving phosphorylation of calpains. Here we tested this hypothesis.…”
mentioning
confidence: 99%
“…Previous studies identified α7 nicotinic acetylcholine receptor (nAChR) as the principal receptor subtype mediating effects of tobacco products and pure nicotine on epithelial cells (Cattaneo et al, 1997;Codignola et al, 1994;Schuller, 1989;Schuller et al, 2000;SchullerOrloff, 1998;Schuller et al, 2003). We have demonstrated that α7 nAChR is essential for a sustained turnover of the mucocutaneous epithelium in humans (Arredondo et al, 2002).…”
Section: Introductionmentioning
confidence: 88%
“…77 Although tobacco smoke components interact with DNA and cause genetic changes, they can also interact with nAchR and activate pathways such as the PI3K/Akt pathway (see below). 78 The biologic effects of nicotine and its metabolites such as NNK are mediated by binding to nicotinic acetylcholine receptors (nAchR), which have been described in many types of cells derived from lung tissue including human bronchial and small airway epithelial cells, 78 pulmonary neuroendocrine cells, 79 neuroepithelial bodies, 80 NSCLC cells 81 and SCLC cells. 82 nAchR are ligand-gated ion channels whose stimulation leads to Ca 2+ influx, and are comprised of 10 alpha and 4 beta subunits.…”
Section: Nicotinic Acetylcholine Receptors (Nachr)mentioning
confidence: 99%
“…In SCLC and pulmonary neuroendocrine cells, nAchR regulate the release of serotonin and cause activation of protein kinase C (PKC), Raf-1, ERK and c-myc. 79 In addition, SCLC has been found to synthesize acetylcholine (the endogenous ligand for nAchR) implicating these receptors in an autocrine loop. 83 nAchR in other cell types may also play a role in the biology of lung cancer, because stimulation of endothelial nAchR by nicotine promotes angiogenesis.…”
Section: Nicotinic Acetylcholine Receptors (Nachr)mentioning
confidence: 99%